Differences in levels of stress, social support, health behaviours, and stress-reduction strategies for women pregnant before and during the COVID-19 pandemic, and based on phases of pandemic restrictions, in Ireland. Issue 5 (September 2021) - Matvienko-Sikar, Karen; Pope, Johanna; Cremin, Avril; Carr, Hayley; Leitao, Sara; Olander, Ellinor K.; Meaney, Sarah
Abstract: Background: The COVID-19 pandemic and related restrictions can adversely impact antenatal maternal well-being and health behaviours. Aim: To examine antenatal stress and stress-reduction strategies, social support, and health behaviours between women pregnant before and during the pandemic in Ireland. Methods: 210 pregnant women were recruited online and in the antenatal department of a tertiary maternity hospital before the pandemic, and 235 women recruited online during the pandemic. Only women resident in Ireland were included in this study. Women completed measures of stress, social support, health-behaviours, and self-reported stress-reduction strategies. Differences in outcomes were examined between women pregnant before and during the pandemic, and between Phase 2 and Phase 3 of the Irish Government COVID-19 restrictions. Findings: Women pregnant during the pandemic reported lower perceived social support, including support from a significant other, friends and family, than women pregnant before the pandemic. There were no significant differences in stress in health behaviours but women reported higher stress and less physical activity during the pandemic. Women reported a range of comparable stress-reduction strategies before and during the pandemic. No differences were observed between phases of pandemic-related restrictions for any outcome. Discussion: Our findings highlight negative impacts of the pandemic on social support, stress, and physical activity, which can have implications for maternal and child health. Lack of differences between restriction phases suggests on-going negative effects for antenatal well-being and behaviours. Conclusion: Development of supports for pregnant women during the pandemic should include social-support and stress-reduction components.